Role of mTOR inhibitor in the cellular and humoral immune response to a booster dose of SARS-CoV-2 mRNA-1273 vaccine in kidney transplant recipients - Pérez-Flores, Isabel; Juarez, Ignacio; Aiffil Meneses, Arianne S.; Lopez-Gomez, Ana; Romero, Natividad Calvo; Rodriguez-Cubillo, Beatriz; Moreno de la Higuera, María Angeles; Peix-Jiménez, Belen; Gonzalez-Garcia, Raquel; Baos-Muñoz, Elvira; Vilela, Ana Arribi; Gómez Del Moral, Manuel; et al. (Frontiers in Immunology, 2023)
Background Immunocompromised patients have an increased risk of developing severe COVID disease, as well as a tendency to suboptimal responses to vaccines. The objective of this study was to evaluate the specific cellular and humoral adaptive immune responses of a cohort of kidney transplant recipients (KTR) after 3 doses of mRNA-1273 vaccine and to determinate the main factors involved. Methods Prospective observational study in 221 KTR (149 non infected), 55 healthy volunteers (HV) and 23 dialysis patients (DP). We evaluated anti-spike (by quantitative chemiluminescence immunoassay) and anti-nucleocapsid IgG (ELISA), percentage of TCD4+ and TCD8+ lymphocytes producing IFNγ against S-protein by intracellular flow cytometry after Spike-specific 15-mer peptide stimulation and serum neutralizing activity (competitive ELISA) at baseline and after vaccination. Results Among COVID-19 naïve KTR, 54.2% developed cellular and humoral response after the third dose (vs 100% in DP and 91.7% in HV), 18% only showed cell-mediated response, 22.2% exclusively antibody response and 5.6% none. A correlation of neutralizing activity with both the IgG titer (r=0.485, p<0.001) and the percentage of S-protein–specific IFNγ–producing CD8-T cells (r=0.198, p=0.049) was observed. Factors related to the humoral response in naïve KTR were: lymphocytes count pre-vaccination >1000/mm3 [4.68 (1.72-12.73, p=0.003], eGFR>30 mL/min [7.34(2.72-19.84), p<0.001], mTOR inhibitors [6.40 (1.37-29.86), p=0.018]. Infected KTR developed a stronger serologic response than naïve patients (96.8 vs 75.2%, p<0.001). Conclusions KTR presented poor cellular and humoral immune responses following vaccination with mRNA-1273. The immunosuppression degree and kidney function of these patients play an important role, but the only modifiable factor with a high impact on humoral immunogenicity after a booster dose was an immunosuppressive therapy including a mTOR inhibitor. Clinical trials are required to confirm these results.